2019
DOI: 10.1140/epjc/s10052-019-7237-y
|View full text |Cite
|
Sign up to set email alerts
|

Topological, noninertial and spin effects on the 2D Dirac oscillator in the presence of the Aharonov–Casher effect

Abstract: In the present paper, we investigate the influence of topological, noninertial and spin effects on the 2D Dirac oscillator in the presence of the Aharonov-Casher effect. Next, we determine the two-component Dirac spinor and the relativistic energy spectrum for the bound states. We observe that this spinor is written in terms of the confluent hypergeometric functions and this spectrum explicitly depends on the quantum numbers n and m l , parameters s and η associated to the topological and spin effects, quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…The DO has been also studied in the context of minimal length uncertainty [33,34]. The DO is an exactly solvable system and this important fact makes the DO is a useful system to determine the influence of spacetime topology on the dynamics of the corresponding systems [5,[35][36][37][38][39][40]. However, in many areas of the modern physics, a quantum oscillator is used to determine the dynamics of the interacting particles [6].…”
Section: Introductionmentioning
confidence: 99%
“…The DO has been also studied in the context of minimal length uncertainty [33,34]. The DO is an exactly solvable system and this important fact makes the DO is a useful system to determine the influence of spacetime topology on the dynamics of the corresponding systems [5,[35][36][37][38][39][40]. However, in many areas of the modern physics, a quantum oscillator is used to determine the dynamics of the interacting particles [6].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the energy levels of the particle and antiparticle depend on the values of the physical parameters involved. In the case of energy (71), its validity is conditioned to Equation (72). Depending on the choice we make for the parameters, we can obtain forbidden energies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no need to solve them here because they have both energy and wave functions similar to those obtained above. Let us study the energies ( 70) and (71). First, we see that the energy E ð>Þ n depends only on the quantum number n and the magnetic field B.…”
Section: Solution Of the Equation Of Motion To E ≠ ±Mmentioning
confidence: 99%
See 2 more Smart Citations